Spycops: secrets and disclosure in the undercover policing inquiry - Schlembach, Raphael (Policy Press, 2024)
The ‘spycops’ scandal has laid bare the existence of secretive police units that sent undercover police officers to infiltrate and undermine hundreds of political campaigns and activist groups. This is the first academic analysis of the activists’ experiences and their attempts to find answers and accountability in the Undercover Policing Inquiry. Written from the perspective of the ‘policed’, the author draws on extensive fieldwork and his first-hand experience of police infiltration through his participation in climate campaigns